ДИАЛЕКТНАЯ ЛЕКСИКА, ФУНКЦИОНИРУЮЩАЯ В СОЦИУМЕ АРХАНГЕЛЬСКОЙ ПРОВИНЦИИ - ПЛЕШКОВА, ТАТЬЯНА (Studia Rossica Posnaniensia, 2006)
The article concerns dialectal vocabulary used nowadays in the Arkhangelsk Region by its native inhabitants. The author analyses semantics and the territorial range of chosen lexemes referring to ‘names o f winds’ taking into consideration age range of the informants.